Repair of Supracondylar Fracture of Femur by Cross Intramedullary Pinning in a Calf - Asif M. Asharaf; Sherin B. Sarangom; Ansiya Iqbal; P. Preena; Varsha Mary Mathai (The Indian Veterinary Journal, 2023)
A 14-day-old female cross-bred Jersey calf was referred for non-weight bearing lameness on the left hind limb following accidental kick by its dam. On orthopaedic examination, the animal evinced pain and crepitus above the stifle joint. Medio-lateral radiograph confirmed the presence of supracondylar fracture (Salter-Harris type II) of left femur. Open reduction and dynamic fixation by cross intramedullary pinning were performed under epidural and general anaesthesia. Postoperative antibiotics, analgesics and regular dressing were advised. Animal started bearing weight during the 2nd postoperative week. Normal weight bearing was observed by the 6th postoperative week.